The handbook of MIS application software testing methods, techniques, and tools for assuring quality through testing - Mosley, Daniel J. (Yourdon Press computing series, 1993)
This guide supplies innovative ideas concerning software quality control and the necessary theoretical and practical considerations of software testing needed by today's data processing practitioners. Features easy-to-understand discussions of software testing methods and contains example test plans designed for real world information systems.